PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIB SDN 011 BUKIT GAJAH KECAMATAN UKUI KABUPATEN PELALAWAN - Suyana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this research was the low mathematics learning outcomes of students. Out of 24 students, only 11 students achieved learning mastery. This study aimed to improve students’ mathematics learning outcomes through the application of the Quantum Teaching model. This research was a Classroom Action Research (CAR) conducted at SD Negeri 011 Bukit Gajah, Ukui District. The data used in this study included teacher and student activity data as well as students’ learning outcomes. Based on the results of the research, both learning outcomes and the activities of teachers and students showed improvement in each cycle. This was evidenced by the increase in the average student learning outcomes, where the initial average score of 63.90 increased to 66.86 in Cycle I, showing an improvement of 2.96 points (4.63%), and further increased in Cycle II to 77.05, showing an improvement of 10.19 points (15.24%). Classical learning mastery in the preliminary data showed that only 13 students (35.71%) achieved the Minimum Mastery Criteria (KKM). In Cycle I, learning mastery increased to 11 students (64.29%), and further increased in Cycle II to 20 students (85.71%) achieving mastery. The improvement in learning outcomes was supported by the increase in teacher activities, where in Cycle I Meeting I the percentage was 70.83% in the good category and increased to 79.17% in Cycle I Meeting II, showing an improvement of 11.76%, while in Cycle II Meeting I the percentage increased to 83.33% in the very good category and further increased to 87.50% in Cycle II Meeting II. Student learning activities also increased, where in Cycle I Meeting I the percentage was 58.33% in the sufficient category and increased to 66.67% in Cycle I Meeting II, showing an improvement of 14.29%, while in Cycle II both meetings reached 83.33% in the good category.